Physical and emotional signs of female and their spouses during pregnancy and the post partum - Jalalmanesh sh (Iran University of Medical Sciences, 1991)
Extract: Whereas pregnancy period in all societies with different cultures cause to physical and emotional and social signs, so Fawcett; York (1985), aim to understand and explain types and how of this physical, emotional and social signs in female and their spouses during primary pregnancy periods and post partum conducted a descriptive study. 70 couples for occurrence type determination of physical, emotional and social signs during primary pregnancy periods and postpartum placed under assessment. 23 female during primary pregnancy periods and 24 female pregnancy last months and 23 post partum's female placed under assessment. In this survey females and their spouses fill a questionnaire with 20 types of physical, emotional and social signs as well as the Beck depression scale.